In vitro and in silico insights on the regulation by gonadal hormones of pituitary GnRH receptor expression in a basal teleost, the European eel - Lin, Chien-Ju; Rousseau, Karine; Chang, Ching-Fong; Dufour, Sylvie (Frontiers in Endocrinology, 2025)
Eel species are basal teleosts with a unique life cycle including an arrest of sexual maturation before the reproductive oceanic migration. Our early studies showed that this blockade results from a deficient production of pituitary gonadotropins, due in part to a low responsiveness to gonadotropin-releasing hormone (GnRH). Three GnRH receptors have been identified in the eel, among them gnrhr2 is the main pituitary receptor whose expression increases during the sexual maturation induced by gonadotropic treatments. We investigated the role of gonadal hormones in the feedback regulation of gnrhr2 expression in the eel. The effects of steroids and activins were tested in vitro on primary cultures of eel pituitary cells and gnrhr2 transcripts measured by qPCR. In silico analysis of eel gnrhr2 promoter was performed to predict transcription factor binding sites and comparisons were made with gnrhr promoters from other teleosts and mammals. Estradiol and testosterone strongly and dose-dependently increased gnrhr2 transcript levels as measured by qPCR. This stimulatory regulation was not observed with a non-aromatizable androgen, 11 keto-testosterone, and the effect of testosterone was abolished in the presence of an aromatase inhibitor, fadrozole, indicating an estrogen-specific positive control of eel gnrhr2 expression. Other steroids, progesterone and cortisol, had no effect on gnrhr2 expression. Gonadal peptides, activins A and B, were also tested, and showed an inhibitory effect on gnrhr2 expression. Our results show that gonadal steroids exert a positive feedback, mediated by estradiol, on pituitary sensitivity to GnRH in the eel, in line with the regulatory mechanisms of the ovulatory luteinizing hormone (LH) surge in mammals. While investigation on gnrhr promoters is significantly lacking outside mammals, in silico analysis of the eel gnrhr2 promoter allowed us to infer transcription factor binding sites potentially involved in the regulation of gnrhr2 expression. Comparison was made with gnrhr promoters from other teleosts and mammals to discuss their evolutionary conservation. This study in the eel, a basal teleost representative, contributes to our understanding of the regulatory mechanisms of the complex eel life cycle and to raise basic knowledge on the regulation and evolution of pituitary GnRH receptivity in vertebrates.